Scientific, scientific-methodological and organizational report “The Institute of theoretical mathematics and scientific computing (ITMandSC) L.N.Gumilyov Eurasian National University in 2019 year (Part III)” - Temirgaliyev, Н. (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2021)
Article contains the Synopsis-Сontent of the textbook "Mathematical analysis". Namely, chapters and paragraphs is entitled, on the one hand, in an expanded form conveying their theme in highlighting the essence and development of ideas, on the other hand, in a brief and informative form. The complete content of the textbook in the form of a Synopsis-Сontent also makes up a complete list of residual knowledge that must be preserved at the subconscious level of the reader.